Osteomyelitis presenting as a swollen elbow in a patient with the acquired immune deficiency syndrome. Issue 8 (August 1988) - Goh, B T; Jawad, A S; Chapman, D; Winceslaus, S J; Forster, G E; Perry, J D
Abstract : A patient suffering from the acquired immune deficiency syndrome (AIDS), who developed swelling of the left elbow four weeks after Staphylococcus aureus septicaemia is reported. The cause was osteomyelitis of the olecranon process.